The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1038/aja.2013.68
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone induced apoptosis in colon cancer cells is regulated by PI3K/Rac1 signaling

Abstract: Recently, it has been reported that testosterone membrane signaling regulates actin reorganization and induces pro-apoptotic responses in colon tumor cells. In the present study the membrane androgen receptors (mARs)-induced activation of Rac1 GTPase and the involvement of PI3K/Rac1 signaling in controlling the apoptotic responses in testosterone treated Caco2 colon cancer cells has been analyzed. In line with previous findings, activation of mAR by testosterone conjugates triggered early and transient actin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…In line with the reports in prostate cancer cells, in the breast cancer cell lines T47D and MDA-MB-231 the testosterone-induced apoptosis was also shown to be mediated by Rho/actin signaling [Pelekanou et al, 2010]. Finally, androgen stimulated actin cytoskeleton reorganization in Caco2 and HCT116 colon tumor cells, controlled by FAK/PI3K/mTOR/PAK1 [Gu et al, 2013] or PI3K/ Rac1 [Alkahtani, 2013] signaling, was also involved in the apoptotic responses [Gu et al, 2009;Alkahtani, 2013], since the drug cytochalasin B or the PI3K inhibitor wortmannin effectively inhibited pro-apoptotic signaling.…”
Section: Glucocorticoid Actions To Actin Reorganization Actin Signalsupporting
confidence: 82%
See 1 more Smart Citation
“…In line with the reports in prostate cancer cells, in the breast cancer cell lines T47D and MDA-MB-231 the testosterone-induced apoptosis was also shown to be mediated by Rho/actin signaling [Pelekanou et al, 2010]. Finally, androgen stimulated actin cytoskeleton reorganization in Caco2 and HCT116 colon tumor cells, controlled by FAK/PI3K/mTOR/PAK1 [Gu et al, 2013] or PI3K/ Rac1 [Alkahtani, 2013] signaling, was also involved in the apoptotic responses [Gu et al, 2009;Alkahtani, 2013], since the drug cytochalasin B or the PI3K inhibitor wortmannin effectively inhibited pro-apoptotic signaling.…”
Section: Glucocorticoid Actions To Actin Reorganization Actin Signalsupporting
confidence: 82%
“…As discussed above, recent observations showed that actin reorganization initiated by steroids hormones, including glucocorticoids and androgens is controlling various cellular functions such as secretion, apoptotic responses and migratory potential in membrane hormone receptor‐stimulated human cancer cells [Charalampopoulos et al, ; Fu and Simoncini, ; Mayanagi et al, ; Papadopoulou et al, ; Gu et al, ; Fu et al, ; Pelekanou et al, ; Alkahtani, ]. These studies clearly establish a pivotal role of actin signaling linking membrane‐initiated, steroid hormone actions and regulation of cellular response mechanisms in different cancer cell types.…”
Section: Introductionmentioning
confidence: 80%
“…However, the effect of androgens in CRC is unclear. In vitro T induced apoptosis in CRC cell lines ( 315 , 368 ), whereas DHEA enhances survival ( 315 ). In contrast, Tutton and Barkla ( 369 ) found that in vivo administration of T accelerated cell proliferation in the small intestine and induced colon cancer in rats, with CRC growth reduced after castration.…”
Section: Dysregulation Of Steroid Sulfation and Desulfationmentioning
confidence: 99%
“…The concentration of sex steroids is one of the most important intrinsic factors that differ between both sexes 3 ; these molecules have important roles in the gut: Estrogens influence epithelial membrane permeability, serotonin production, expression of tight junctions, inflammation, and microbiome composition 4 ; Androgens are poorly understood; however, in a mouse model alters the proliferation of enterocytes and increases the size of crypts 5 . Further in vitro studies with colon cancer cell lines such as DLD-1, HCT-116, SW480, and CaCO2 have shown that estradiol reduces the viability of these cells, and testosterone (T4) and dihydrotestosterone (DHT) increase the apoptosis in CaCO2 and HCT116 [6][7][8][9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%